Seroprevalence of dengue, Zika, and chikungunya in São Sebastião, Brazil (2020–2021): a population-based survey - Nobre, Tayane Ferreira (2025)
This study was funded by the Sentinela International joint laboratory (LMI Sentinela), a formal partnership between the French National Research Institute for Sustainable Development (Institut de Recherche pour le Développement, IRD), the University of Brasília (UnB), and the Oswaldo Cruz Foundation (Fiocruz). Additional funding was provided by the Coordination for the Improvement of Higher Education Personnel (CAPES), the Ministry of Education, Brazil—Finance Code 001, and the Pan-American Health Organization (PAHO).